Pressurized intraluminal aerosol chemotherapy with Dbait in the distal esophagus of swine - Khalili-Harbi, Nadja; Herath, Nirmitha; Solass, Wiebke; Giger-Pabst, Urs; Dutreix, Marie; Reymond, Marc Andre (Endoscopy, 2016)
Background and study aims: A novel therapeutic concept, pressurized intraluminal aerosol chemotherapy (PILAC), and a corresponding device for distributing drugs to the mucosa and submucosa of the distal esophagus are presented. Materials and methods: The endoscopic device that was designed consisted of (i) a double-balloon catheter, similar to a Sengstaken-Blakemore tube; (ii) a carbon dioxide (CO2) line, used to create a gaseous, pressurized environment; and (iii) a micropump, used to generate a therapeutic aerosol. The device was inserted into the distal esophagus in three narcotized Landrace pigs. Dbait (short interfering DNA, or siDNA) was aerosolized under pressure (12 mmHg) in CO2 at 37 °C for 30 minutes. Results: The procedure was well tolerated by all animals. At autopsy, no mucosal or muscular tear was observed. Fluorescence microscopy revealed a homogeneous intramural distribution of Dbait–cyanine 5 in the esophageal wall down to the circular muscular layer (400 – 600 µm).Conclusions: PILAC is feasible in a large animal model and appears to be safe. Therapy of the entire “tissue at risk” for the development of cancer in the distal esophagus is possible without the prior endoscopic identification of diseased tissue.